2011
DOI: 10.1002/j.2161-0045.2011.tb00976.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Initial Psychometric Evaluation of the Korean Career Stress Inventory for College Students

Abstract: The purpose of this study was to develop a Korean College Stress Inventory (KCSI), which is designed to measure Korean college students' experiences and symptoms of career stress. Even though there have been numerous scales related to career issues, few scales measure the career stress construct and its dimensions. Factor structure, internal consistency, and concurrent validity of the KCSI scores are described. Results indicated that the internal consistency reliabilities of 4 KCSI subscale scores were reasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 31 publications
4
31
0
2
Order By: Relevance
“…Responses were given on a 5-point Likerttype scale (1 = strongly disagree to 5 = strongly agree; higher scores indicate greater stress). The subscale had good reliability (α = .89 and .92 in two studies) and validity with Korean students (e.g., correlated with lack of self-identity); (Choi et al, 2011;Kim et al, 2014). In the current study, we confirmed that the translated scale had a one-factor structure by using CFA.…”
Section: Methodssupporting
confidence: 75%
“…Responses were given on a 5-point Likerttype scale (1 = strongly disagree to 5 = strongly agree; higher scores indicate greater stress). The subscale had good reliability (α = .89 and .92 in two studies) and validity with Korean students (e.g., correlated with lack of self-identity); (Choi et al, 2011;Kim et al, 2014). In the current study, we confirmed that the translated scale had a one-factor structure by using CFA.…”
Section: Methodssupporting
confidence: 75%
“…Because career development is a lifelong process and not a one‐time decision (Super, 1990), individuals are engaged in continuous decision‐making processes at different stages of their lives. The reduced predictability and stability of the job market have made career choice and related decisions more difficult and complicated (B. Y. Choi, Park, Nam, Lee, & Lee, 2011).…”
mentioning
confidence: 99%
“…The reduced predictability and stability of the job market have made career choice and related decisions more difficult and complicated (B. Y. Choi, Park, Nam, Lee, & Lee, 2011). As a consequence, an increasing number of individuals have been seeking professional help for their career concerns (Lester & Frugoli, 1989).…”
mentioning
confidence: 99%
“…Kim, Jung, et al () confirmed the factor structure of the Korean version of the PHCI by conducting exploratory factor analysis and CFA, and the internal consistency of the subscale scores ranged from .76 to .90. The convergent validity for the PHCI was demonstrated through its significant correlations with career‐related scales, including career stress (Choi et al, ), career decision self‐efficacy (Betz et al, ; Kim, Jang, et al, ), and career preparation behavior (Kim & Kim, ).…”
Section: Methodsmentioning
confidence: 99%